CRISPR/Cas9 mutagenesis of the Arabidopsis GROWTH-REGULATING FACTOR (GRF) gene family - Angulo, Juan; Astin, Christopher P.; Bauer, Olivia; Blash, Kelan J.; Bowen, Natalee M.; Chukwudinma, Nneoma J.; DiNofrio, Austin S.; Faletti, Donald O.; Ghulam, Alexa M.; Gusinde-Duffy, Chloe M.; Horace, Kamaria J.; Ingram, Andrew M.; et al. (Frontiers in Genome Editing, 2023)
Genome editing in plants typically relies on T-DNA plasmids that are mobilized by Agrobacteriummediated transformation to deliver the CRISPR/Cas machinery. Here, we introduce a series of CRISPR/Cas9 T-DNA vectors for minimal settings, such as teaching labs. Gene-specific targeting sequences can be inserted as annealed short oligonucleotides in a single straightforward cloning step. Fluorescent markers expressed in mature seeds enable reliable selection of transgenic or transgenefree individuals using a combination of inexpensive LED lamps and colored-glass alternative filters. Testing these tools on the Arabidopsis GROWTH-REGULATING FACTOR (GRF) genes, we were able to create a collection of predicted null mutations in all nine family members with little effort. We then explored the effects of simultaneously targeting two, four and eight GRF genes on the rate of induced mutations at each target locus. In our hands, multiplexing was associated with pronounced disparities: while mutation rates at some loci remained consistently high, mutation rates at other loci dropped dramatically with increasing number of single guide RNA species, thereby preventing a systematic mutagenesis of the family. Deleted: CRISPR/Cas complexes can be programmed to bind 201 virtually any DNA sequence and thus enable applications as diverse 202 as chemical modification of target DNA, directed manipulation of 203 gene transcription, or genome editing by homologous recombination 204